Knowledge and perceptions about ante natal care services by pregnant women at Julesburg local area, Mopani District in Limpopo Province - Maluleke, Lucy (My University, 2017)
Background: Ante natal care (ANC) service is a very important intervention to track the progress and to identify complications that might arise during pregnancy. The first ANC visit at a health facility is even more important as health providers are able to identify whether there are any risks to the mother and the unborn child and it should be initiated at the 1st trimester of pregnancy. Objectives: The study aim was to establish the knowledge and perceptions about ANC services among pregnant women in the Julesburg Local Area in the Mopani District of Limpopo Province. Methods: A quantitative cross-sectional research approach was used at six primary health care facilities in the Julesburg Local Area of the Mopani District in Limpopo Province. Stratified random sampling was used. Data were collected from 293 pregnant women using a self-administered questionnaire. . Data analysis was done using the International Business Management Statistical Package for Social Sciences 23 (SPSS 23). Results: The results reveal that a high percentage of pregnant women have adequate knowledge with regard to ANC services. The results further show that knowledge level of pregnant women has no association with educational level (P=0.488). With regard to perception, half of the respondents have positive perceptions of ANC services, while a further half have negative perceptions of these services. Conclusion: ANC service is of great importance to further reduce maternal and neonatal deaths as most of these deaths are avoidable. There is a need to strengthen the training programme of staff by providing further training exposure and health information to pregnant women with regard to the important of early ANC initiation and frequency of ANC visit need to be intensified. Keywords: Health care workers, antenatal care, knowledge, perception, initiation, utilization.
Thesis (MPH.) -- University of Limpopo, 2017.
Keywords: Antenatal care; Health care workers; Maternal health services; Prenatal care; Pregnancy -- Complications